Intermediates in the cleavage of endoperoxides†. (14th July 2016) - Bauch, Marcel; Klaper, Matthias; Linker, Torsten; Abe, Manabu; Sheridan, Robert S.
Abstract : The decomposition of anthracene endoperoxides has been investigated under various conditions. Thermolyses proceed via radical intermediates and afford anthracenes andrearrangement products, depending on the substitution pattern. Interestingly, not only the O–O but also the C–O bond can be cleaved homolytically. Under basic conditions fragmentations take place, affording anthraquinone, andreactive oxygen species . This mechanism explains the often observed decomposition of endoperoxides during work‐up. Finally, an acid‐catalyzed cleavage has been observed under release ofhydrogen peroxide . The results should be interesting for the mechanistic understanding of peroxide decomposition and the endoperoxides might serve as mild sources ofreactive oxygen species for future applications. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Endoperoxides1 are cleaved under various conditions by different pathways, resulting in several intermediates, depending on substituents R. Thermolysis proceeds via radicals, whereas bases or acids afford alkoxides or carbenium ion intermediates. Parental anthracenes2, anthraquinone3, or reactive oxygen species4 and5 have been isolated or detected as products, opening the door to tailored sources of reactive oxygen species.